2020
DOI: 10.1080/23311886.2020.1812831
|View full text |Cite
|
Sign up to set email alerts
|

Palm oil social conflict resolution and mediation in Jambi

Abstract: The increase of oil palm plantation and manufacturing in Jambi offers any environmental and social problems, leading to conflict between companies and the local community. In addition, some conflict in there not yet resolved, and for achieving conflict resolution need to understand each element that affects the conflict and offer proper conflict resolution. This research identified and analyzed each element that offers the effect to conflict resolution based on mass media information, literature review, and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 42 publications
1
8
0
1
Order By: Relevance
“…This was exactly what initially happened in the Bebidas case. The results of this study are also in line with the findings of Fisher et al (2020), Rokhim et al (2020), Riggs et al (2016) that limited knowledge and understanding of regulations, social conditions, and scientific-based knowledge have caused forest communities to lose in case of disputes/conflicts, especially with authorities and/or corporations related to land and natural resource management. The existence of 'resource' support in various contexts is also a capacity that results from collaborative action.…”
Section: Capacity For Joint Actionsupporting
confidence: 88%
“…This was exactly what initially happened in the Bebidas case. The results of this study are also in line with the findings of Fisher et al (2020), Rokhim et al (2020), Riggs et al (2016) that limited knowledge and understanding of regulations, social conditions, and scientific-based knowledge have caused forest communities to lose in case of disputes/conflicts, especially with authorities and/or corporations related to land and natural resource management. The existence of 'resource' support in various contexts is also a capacity that results from collaborative action.…”
Section: Capacity For Joint Actionsupporting
confidence: 88%
“…Therefore, oil palm became one of the leading commodities in Jambi that can support local income sources [4]. Although the province has extensive oil palm plantations, there are many overlapping issues or inconsistencies with various policies [5].…”
Section: Introductionmentioning
confidence: 99%
“…Palm‐oil plantations have been noted to contribute to local economies by creating jobs, promoting local infrastructure, and helping to alleviate rural poverty 3–5 . However, various sources have reported that land grabbing from corporations to enable large‐scale biofuel production can lead to social conflict between locals and companies 6–8 . Such environmental and social drawbacks of biofuel production are often overlooked as countries gain various economic benefits.…”
Section: Introductionmentioning
confidence: 99%